Women and Politics: Women’s Participation in The Indonesian National Political Movement, 1923 -1942 - Siswantari, Siswantari; Abdurakhman, Abdurakhman; Mulyatari, Dwi; Haghia, Raisye Soleh; Rahman, Syahidah Sumayyah (Paramita: Historical Studies Journal, 2024)
This study aims to analyze women’s political participation during the national movement. The movement period began the women’s movement to voice their political ideas towards independence.    The women’s political movement has long existed. Women have struggled to establish their existence since colonial times. Analysis of women’s participation efforts in the political field is described in three organizations from three cities, namely Batavia (Jakarta), Jogjakarta, and Medan, each through Perhimpoenan Kaoem Betawi representing regional organizations, Aisyiyah representing socio-religious organizations and Keoetamaan Isteri representing socio-political organizations. This research uses historical heuristics, criticism, interpretation, and historiography methods. The heuristic stage is carried out by searching for library sources, documents, and archives, and it is selected based on the source criticism carried out. The results show that the wishes and demands for women’s political participation have not been realized. The limited opportunities for women to sit in the Volksraad and direct competition with men were factors that did not directly result in women being involved in politics. Penelitian ini bertujuan untuk menganalisis partisipasi politik perempuan pada masa pergerakan nasional. Masa pergerakan mengawali gerakan perempuan untuk menyuarakan ide-ide politiknya menuju kemerdekaan. Gerakan politik perempuan sudah ada sejak lama. Perempuan telah berjuang untuk membangun eksistensinya sejak zaman kolonial. Analisis terhadap upaya partisipasi perempuan dalam bidang politik digambarkan pada tiga organisasi dari tiga kota, yaitu Batavia (Jakarta), Jogjakarta, dan Medan, masing-masing melalui Perhimpoenan Kaoem Betawi yang mewakili organisasi daerah, Aisyiyah yang mewakili organisasi sosial keagamaan, dan Keoetamaan Isteri yang mewakili organisasi sosial-keagamaan. organisasi politik. Penelitian ini menggunakan metode sejarah yang terdiri atas heuristik, kritik, interpretasi, dan historiografi. Tahap heuristik dilakukan dengan mencari sumber perpustakaan, dokumen, dan arsip, serta dipilih berdasarkan kritik sumber yang dilakukan. Hasilnya menunjukkan bahwa keinginan dan tuntutan partisipasi politik perempuan belum terwujud. Terbatasnya kesempatan perempuan untuk duduk di Volksraad dan persaingan langsung dengan laki-laki menjadi faktor yang tidak secara langsung menyebabkan perempuan terlibat dalam politik.